Pharmacotherapy-Based Problems in the Management of Diabetes Mellitus: Needs Much More to be Done! - Ali, N (Medknow Publications, 2010)
A total of 856 diabetic patients were evaluated for pharmacotherapy-based problems like for possible drug interactions, adverse drug reactions, and other mismatches, if any. Poor correlation between the advised insulin therapy and patients’ fasting blood glucose levels (12%, n=103) was observed. To most of the patients (41.66%, n= 357), insulin therapy was advised in combination with glucocorticoides, thiazides diuretics, and propranolol. Prescribing beta blocker (propranolol) with insulin is contraindicated. The higher incidence of diabetic foot patients was in the mean age of 57±3.4 years that was controlled with combination therapy of insulin and oral antidiabetics (63.0%, n=516). 11.1% of the treated patients could not take the prescribed therapy due to poor acceptance of insulin therapy due to its syringe needle prick. 41.66% risks of potential drug interactions, 7.93% adverse drug reactions, and 6.6% mismatches were recorded, as per the international approved algorithm, for managing a diabetes mellitus that reflects poor health care system. All these events necessitate for coordinating with other health professionals to make the therapy safer in the better interest of the patients. It is concluded that in practice prescribing pattern carries more risks for patients. It is imperative to improve the practice of pharmacotherapeutics rather than to practice in routine.